How Rumors are Associated with Retail Investors’ Investment Decision Making - Tin, Shin Thed (2023)
Retail investors’ decision-making process can become complex, causing them to rely on rumors to make investment decisions. However, research on rumors and retail investment decision-making in Malaysia is still lacking. This study aims to explore rumors from a social reality perspective, the source that facilitates rumors, and the association between rumors and retail investors’ investment decision-making. Bursa Malaysia was selected as the target exchange for this study to understand how the process of retail investors’ decision-making when it is associated with rumors. In the data collection process, this study embarked on a qualitative inquiry approach using Gioia methodology. A semi-structured interviews with 29 respondents was conducted using purposive sampling for the fieldwork. Data-structure analysis reveals four aggregate dimensions of how rumors are associated with retail investors’ investment decision-making, namely anticipated outcome, subjective probability, external factors, and fundamental principles. This study shows that rumor matters at the level of sociological influence, the mechanism of rumor spread, and the psychological perspective. These dimensions are associated with rumors and the investment decisions of retail investors. This study contributes to a better understanding of behavioral finance in retail investors' decision-making and its implications for the National Sustainable Development Goals (SDGs) program from a societal impact perspective. This study could also be a starting point for Bursa Malaysia and the Securities Commission Malaysia to investigate the actual existence of rumors, effective strategies to manage them, and their impact on the stock market and retail investors' investment decision making.